(untitled) (GIST – Education and Learning Research Journal, 2012)
The present article seeks to encourage reflection on the characteristics and considerations when implementing Content and Language Integrated Learning (CLIL) in a diverse context such as the Colombian one. Initially, the general aspects of an innovative and changing education in a globalized world are presented by stating the need to innovate. Secondly, Content and Language Integrated Learning is defined along its implications by critically addressing CLIL dimensions. Lastly, the article offers a broad view about the inclusion of CLIL in the Colombian context. In general, the article presents the implications about the use of CLIL, specifically its dimensions and influence in Colombia.